How to connect with your audience (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. All of us are bombarded with too many articles to read and too many videos to watch. Your audience - and by that, we mean readers, watchers and listeners - make the decision to follow or reject you in a microsecond. But what would it be like if you understood how they chose? This track focuses on the three factors an audience wants from a speaker. Once you know them, you're guaranteed a bigger and more loyal audience for all your hard work. Learning Objectives Learn how to establish your personal credibility with an audience Learn how to create an emotional bond with an audience Learn how to convince an audience with evidence and storytelling.